2019
DOI: 10.1186/s13098-019-0451-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic associations between Transcription Factor 7 Like 2 rs7903146 polymorphism and type 2 diabetes mellitus: a meta-analysis of 115,809 subjects

Abstract: Background Some genetic association studies tried to investigate potential associations of Transcription Factor 7 Like 2 ( TCF7L2 ) rs7903146 polymorphism with type 2 diabetes mellitus (T2DM). However, the results of these studies were not consistent. Thus, we performed the present meta-analysis to explore associations between TCF7L2 rs7903146 polymorphism and T2DM in a larger pooled population. Methods Systematic li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
(23 reference statements)
2
9
1
Order By: Relevance
“…Anjum et al [16] in Chinese population, Danquah et al [17] in Ghanaian population, Ezzidi et al [18] in Tunisian population, and Assmann et al [19] in Brazilian population came to the same conclusion of the significance of association of the TCF7L2 rs7903146 (C/T) polymorphism and T2DM susceptibility, especially the homozygous TT genotype. A meta-analysis conducted by Lou et al [20] on subjects from different ethnic groups showed a positive correlation of the rs7903146 C/T SNP with T2DM, and this agrees with a previous meta-analysis made by Ding et al [21].…”
Section: Discussionsupporting
confidence: 89%
“…Anjum et al [16] in Chinese population, Danquah et al [17] in Ghanaian population, Ezzidi et al [18] in Tunisian population, and Assmann et al [19] in Brazilian population came to the same conclusion of the significance of association of the TCF7L2 rs7903146 (C/T) polymorphism and T2DM susceptibility, especially the homozygous TT genotype. A meta-analysis conducted by Lou et al [20] on subjects from different ethnic groups showed a positive correlation of the rs7903146 C/T SNP with T2DM, and this agrees with a previous meta-analysis made by Ding et al [21].…”
Section: Discussionsupporting
confidence: 89%
“…23 So far, the data suggest that the allelic frequencies of the rs7903146 SNP and possibly, the effect size of this SNP are variable worldwide. 14 Regarding the Greek population, apart from a study by Katsoulis et al 36 in which the role of TCF7L2 variants in the development of impaired glucose metabolism (including impaired fasting glucose [IFG] or T2DM) in patients with metabolic syndrome (MS) was investigated, the present study is the first report of an association between TCF7L2 rs7903146 variants and prediabetes/T2DM. Christopoulos et al 37 investigated the role of the rs7903146 variant in women with polycystic ovary syndrome, while Pappa et al 38 and Potasso et al 39 examined the association with gestational diabetes mellitus (GDM).…”
Section: Discussionmentioning
confidence: 85%
“…23 So far, the data suggest that the allelic frequencies of the rs7903146 SNP and possibly, the effect size of this SNP are variable worldwide. 14 Regarding the Greek population, apart from a study by Katsoulis et al 36 in which the role of TCF7L2 variants in the In the present study, the participants were separated into two subgroups based on their HbA1c levels. One subgroup comprised of patients exhibiting normal HbA1c values (HbA1c< 5.7%) while the other subgroup consisted of patients identified with hyperglycemia (HbA1c ≥ 5.7%).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Authors additionally noted that there is also an elevated proinsulin to insulin ratio. Meta-analysis on 115,809 subjects [10] based on 68 studies also revealed that there is a strong association between T2D and the rs7903146 polymorphism.…”
Section: Introductionmentioning
confidence: 95%